2016
DOI: 10.1051/0004-6361/201527833
|View full text |Cite
|
Sign up to set email alerts
|

The radio continuum spectrum of Mira A and Mira B up to submillimeter wavelengths

Abstract: Aims. We present new measurements of the flux densities at submillimeter wavelengths based on ALMA band 7 (338 GHz, λ0.89 mm) and band 9 (679 GHz, λ0.44 mm) observations to better constrain the origin of the continuum emission of the Mira AB binary system and to check its orbit. Methods. We have measured the Mira A and Mira B continuum in ALMA band 7, with a resolution of ∼0. 31, and for the first time in ALMA band 9, with a resolution of ∼0. 18. We have resolved the binary system at both bands, and derived th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…The spectral index in the radio wavelengths is found to be 1.86(≈2), close to the Rayleigh-Jeans law at low frequencies of an optically thick blackbody (Reid & Menten 1997a). Matthews et al (2015) and Planesas et al (2016) found that this spectral index can also fit well the submillimetre flux densities of o Cet at 338 GHz in ALMA Band 7 and at 679 GHz in ALMA Band 9, respectively.…”
Section: Previous Observationssupporting
confidence: 63%
“…The spectral index in the radio wavelengths is found to be 1.86(≈2), close to the Rayleigh-Jeans law at low frequencies of an optically thick blackbody (Reid & Menten 1997a). Matthews et al (2015) and Planesas et al (2016) found that this spectral index can also fit well the submillimetre flux densities of o Cet at 338 GHz in ALMA Band 7 and at 679 GHz in ALMA Band 9, respectively.…”
Section: Previous Observationssupporting
confidence: 63%
“…Recently, the short distance environment of Mira A+B has been observed using the Atacama Large Millimetre/submillimetre Array (ALMA). Continuum emission has been observed at 1, 3 and 7 mm wavelength and its analysis (Vlemmings et al 2015;Planesas et al 2016), in particular in association with JVLA observations (Matthews et al 2015), has resolved Mira A photosphere with unprecedented spatial resolution. The 12 CO(3-2) line emission has been mapped with an also unprecedented spatial resolution of ∼0.5 ′′ up to a distance of ∼10 ′′ from the central star by Ramstedt et al (2014).…”
Section: Introductionmentioning
confidence: 77%
“…32 in the combined data. The observations are described in Planesas et al (2016). Four spectral ranges were observed: 330.4−330.7 and 345.6−345.9 GHz − at a velocity resolution of 0.1 km s −1 − and 331.1−332.8 and 343.7−345.5 GHz, at a velocity resolution of about 13.6 km s −1 .…”
Section: Almamentioning
confidence: 99%